Exploring sustainable behavior structure in higher education a socio-psychology confirmatory approach - Juarez-Najera, Margarita (Springer International Publishing, 2015)
This book presents a social-psychology model delineating the factors that may influence in an altruistic manner sustainable behaviour (SB) of students, faculty and administrators in four higher education institutions (HEI) with very different economic and social characteristics. It presents the areas where these individuals work (education and community management), and in which of them education for sustainability is promoted, focusing on four alternative methods of learning: play, art, group therapy, and personnel management. The book is intended for bachelors and graduated students, as well as researchers in social psychology, environmental psychology, conservation psychology, environmental education, education for sustainable development, cross-cultural psychology, and social sciences